Silencing Myeloid Netrin-1 Induces Inflammation Resolution and Plaque Regression. Issue 5 (22nd July 2021) - Schlegel, Martin; Sharma, Monika; Brown, Emily J.; Newman, Alexandra A.C.; Cyr, Yannick; Afonso, Milessa Silva; Corr, Emma M.; Koelwyn, Graeme J.; van Solingen, Coen; Guzman, Jonathan; Farhat, Rubab; Nikain, Cyrus A.; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Rationale: Therapeutic efforts to decrease atherosclerotic cardiovascular disease risk have focused largely on reducing atherogenic lipoproteins, yet lipid-lowering therapies alone are insufficient to fully regress plaque burden. We postulate that arterial repair requires resolution of a maladaptive immune response and that targeting factors that hinder inflammation resolution will facilitate plaque regression. Objective: The guidance molecule Ntn1 (netrin-1) is secreted by macrophages in atherosclerotic plaques, where it sustains inflammation by enhancing macrophage survival and blocking macrophage emigration. We tested whether silencing Ntn1 in advanced atherosclerosis could resolve arterial inflammation and regress plaques. Methods and Results: To temporally silence Ntn1 in myeloid cells, we generated genetically modified mice in which Ntn1 could be selectively deleted in monocytes and macrophages using a tamoxifen-induced CX3CR1-driven cre recombinase ( Ntn1 fl/fl Cx3cr1 creERT2+ ) and littermate control mice ( Ntn1 fl/fl Cx3cr1 WT ). Mice were fed Western diet in the setting of hepatic PCSK9 (proprotein convertase subtilisin/kexin type 9) overexpression to render them atherosclerotic and then treated with tamoxifen to initiate deletion of myeloid Ntn1 (Mø ΔNtn1 ) or not in controls (Mø WT ). Morphometric analyses performed 4 weeks later showed that myeloid Ntn1 silencing reduced plaque burden in the aorta (−50%) and plaque complexity in the aortic root. Monocyte-macrophage tracing experiments revealed lower monocyte recruitment, macrophage retention, and proliferation in Mø ΔNtn1 compared with Mø WT plaques, indicating a restructuring of monocyte-macrophage dynamics in the artery wall upon Ntn1 silencing. Single-cell RNA sequencing of aortic immune cells before and after Ntn1 silencing revealed upregulation of gene pathways involved in macrophage phagocytosis and migration, including the Ccr7 chemokine receptor signaling pathway required for macrophage emigration from plaques and atherosclerosis regression. Additionally, plaques from Mø ΔNtn1 mice showed hallmarks of inflammation resolution, including higher levels of proresolving macrophages, IL (interleukin)-10, and efferocytosis, as compared to plaques from Mø WT mice. Conclusion: Our data show that targeting Ntn1 in advanced atherosclerosis ameliorates atherosclerotic inflammation and promotes plaque regression.